(untitled) (Research, Society and Development, 2022)
With the growth of commercialization and ingestion of mangoes, problems related to the reduction of shelf life and the presence of pathogenic microorganisms that cause diseases transmitted by food were observed. In this sense, the producer market makes use of synthetic chemicals in food on a large scale. As an alternative method, the application of essential oils for microbiological and antioxidant control has shown promise. Thus, the objective of this work is to describe the studies that evaluated the action of the use of essential oils in the conservation and extension of the post-harvest shelf life of mangoes. For this purpose, the descriptors “mangoes coated with essential oils”, “shelf life”, “post-harvest validity of mangoes”, “essential oils in mangoes”, “essential oils in the conservation of mangoes”, “use of essential oils in mangoes as conservation methods”, “essential oils in mangoes” and “mango and shelf life with essential oils”. A bibliographic survey was carried out using the Google Scholar databases, Platform for the Coordination for the Improvement of Higher Education Personnel (CAPES), Scientific Electronic Library (SciELO) and ScienceDirect, delimiting the articles from 2012 to 2023 in 2 languages: Portuguese and English. Through the study carried out, using 15 articles, it was noticed that the best method is the application of coating containing essential oils, especially thyme oil, which showed better results, extending the shelf life of mangos by up to 26 ± 2 days. Therefore, essential oils associated or not with other substances are effective in promoting antimicrobial activity, delaying maturation and, thus, prolonging the conservation of post-harvest mangoes.